Harm reduction outcomes and practices in Housing First: A mixed-methods systematic review. (1st November 2021) - Kerman, Nick; Polillo, Alexia; Bardwell, Geoff; Gran-Ruaz, Sophia; Savage, Cathi; Felteau, Charlie; Tsemberis, Sam
Abstract: Background: Harm reduction is a central tenet of Housing First. As the intervention has been shown to stably house people experiencing chronic homelessness across the lifespan with complex behavioural health needs, it is critical to understand the harm reduction outcomes and practices in Housing First. Methods: A systematic review following PRISMA guidelines was conducted of five databases: PsycINFO, MEDLINE, Embase, CINAHL, and Google Scholar. Harm reduction outcomes and practices in Housing First were examined in four domains: substance-related harms, viral health, sexual health, and harm reduction service use. Results: A total of 35 articles were included in the review, 23 of which examined harm reduction outcomes and 12 of which investigated harm reduction practices in Housing First. Harm reduction outcome studies focused mostly on nonspecific substance use problems, with Housing First being found to have minimal effects in this domain. More severe harms, such as delirium tremens and substance use-related deaths, have been minimally explored, though preliminary evidence is promising. Viral health, sexual health, and harm reduction service use outcomes were the focus of few studies. Research on harm reduction practices highlighted that Housing First providers experience both flexibility and ambiguity in their work using a harm reduction approach, and the importance of empathetic working relationships for engagement in harm reduction work. Conclusions: Harm reduction outcomes in Housing First remain underexamined and any conclusions of the intervention's impacts in this domain would be premature. Effective harm reduction practices in Housing First require strong working relationships between staff and tenants. Highlights: Research on harm reduction outcomes in Housing First is narrow in scope. Housing First does not enable substance use harms. Findings on severe substance-related harms are promising albeit preliminary. Housing First providers experience flexibility and ambiguity with harm reduction. Strong working relationships are essential to engagement in harm reduction work.